Finite-time stabilization of switched stochastic nonlinear systems with mixed odd and even powers. (November 2016) - Huang, Shipei; Xiang, Zhengrong
Abstract: This paper investigates the finite-time stabilization of a class of switched stochastic nonlinear systems in p -normal form, where the power orders of the system are dependent upon the switching signal and the system structure is in non-triangular form. Compared with the existing results, some power orders of the system are allowed to be even. Under suitable assumptions, a state feedback control law with state-dependent switching is designed by using the convex combination method and the adding a power integrator technique. It is shown that the resulting closed-loop system is finite-time stable in probability. Simulation results of a continuously stirred tank reactor (CSTR) system are provided to show the effectiveness and applicability of the proposed method.